Assembling the dominant accounts of youth drug use in Australian harm reduction drug education - Farrugia, Adrian (Elsevier BV, 2014)
Education programs are a central element of Australian harm reduction drug policy. Considered less judgmentaland more effective than the punitive policies of Australia’s past, harm reduction drug educationis premised on the goal of reducing ‘risks’ and harms associated with illicit drug use rather than an eliminationof use per se. In this article I analyse two sets of key texts designed to reduce drug related harmin Australia: harm reduction teaching resources designed for classroom use and social marketing campaignsthat are targeted to a more general audience. I identify two significant accounts of young people’sdrug use present in Australian harm reduction drug education: ‘damaged mental health’ and ‘distress’. Ithen draw on some of Deleuze and Guattari’s key concepts to consider the harm reducing potential theseaccounts may have for young people’s drug using experiences. To demonstrate the potential limitationsof current drug education, I refer to an established body of work examining young people’s experiencesof chroming. From here, I argue that the accounts of ‘damaged mental health’ and ‘distress’ may work tolimit the capacity of young drug users to practice safer drug use. In sum, current Australian harm reductiondrug education and social marketing may be producing rather than reducing drug related harm.